1989
DOI: 10.1042/bj2630867
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of α-linolenic acid through the mitochondrial outer membrane in the rat liver and influence on the rate of oxidation. Comparison with linoleic and oleic acids

Abstract: The movement of alpha-linolenic acid (C18:3, n-3) through the mitochondrial outer membrane to oxidation sites was studied in rat liver and compared with the movement of linoleic acid (C18:2, n-6) and oleic acid (C18:1, n-9). All differ in the degree of unsaturation, but have the same chain length and the same position of the first double bond when counted from the carboxyl end. The following results were obtained. (1) The overall beta-oxidation in total mitochondria was in the order C18:3, n-3 greater than C18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 25 publications
1
33
0
1
Order By: Relevance
“…Once in the hepatocytes, catabolism of FA is mostly directed towards synthesis of ketone bodies for energy utilisation by tissues (Reid and Husbands, 1985) as observed in our study in which products of LA and ALA oxidation were dominated by ASPs (.97% of total oxidation products). The higher rate of oxidation of ALA compared with that of LA is in agreement with previous data on rats (Clouet et al, 1989;Emmison et al, 1995) that showed that the rate of hepatic mitochondrial oxidation of 18:3n-3 was higher than that of 18:2n-6 mainly due to higher mitochondrial activity of carnitine palmitoyltransferase (Ide et al, 1996). As ALA is an essential FA, the extent of its partitioning towards b-oxidation is somewhat counterintuitive.…”
Section: Discussionsupporting
confidence: 81%
“…Once in the hepatocytes, catabolism of FA is mostly directed towards synthesis of ketone bodies for energy utilisation by tissues (Reid and Husbands, 1985) as observed in our study in which products of LA and ALA oxidation were dominated by ASPs (.97% of total oxidation products). The higher rate of oxidation of ALA compared with that of LA is in agreement with previous data on rats (Clouet et al, 1989;Emmison et al, 1995) that showed that the rate of hepatic mitochondrial oxidation of 18:3n-3 was higher than that of 18:2n-6 mainly due to higher mitochondrial activity of carnitine palmitoyltransferase (Ide et al, 1996). As ALA is an essential FA, the extent of its partitioning towards b-oxidation is somewhat counterintuitive.…”
Section: Discussionsupporting
confidence: 81%
“…This may reflect lower muscle mass in women, and the potential overall effect would be to increase availability of αLNA for conversion to longer chain PUFA in women compared to men. The extent of partitioning of αLNA towards β-oxidation, when assessed under identical conditions, was almost twice that of palmitic, stearic and oleic acids [29], which may reflect the higher affinity of carnitine palmitoyl trasnsferase-1 for αLNA [32]. Since αLNA is essential in the human diet, this finding is somewhat counterintuitive and there is currently no explanation for the preferential use of αLNA as an energy source.…”
Section: Disposal Of α-Linolenic Acidmentioning
confidence: 40%
“…While there are advantages in terms of safety, there are unresolved issues regarding standardisation of quantification of data (particularly how conversion between fatty acids should be estimated), kinetic modelling, variation between subjects including age and gender, the method of administration of the labelled fatty acid, the duration of the study, the extent to which the background diet is controlled and the use of measurements of labelled fatty acids in blood (including which lipid pool should be measured) as a marker of fatty acid metabolism within tissues [53]. Together these factors have resulted in considerable heterogeneity in the findings of studies of αLNA metabolism in humans using stable isotope tracers [21,23,25,27,32,[54][55][56][57]. This presents a considerable challenge to any attempt to reach a consensus view on αLNA metabolism in man.…”
Section: Estimates α-Linolenic Acid Conversion From Stable Isotope Trmentioning
confidence: 99%
“…17,18 Although fat intake 19,20 and genotype 21,22 interact to regulate fat deposition, there are both in vitro 1,23 and in vivo 24,25 data which suggest that dietary fatty acid composition modulates to some extent the partitioning of fat between oxidation and storage.…”
Section: Discussionmentioning
confidence: 99%